2016
DOI: 10.1111/clr.12812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static magnetic fields on bone regeneration of implants in the rabbit: micro‐CT, histologic, microarray, and real‐time PCR analyses

Abstract: μCT, histology, microarrays, and real-time PCR indicate that SMFs could be an effective approach to improving bone regeneration around dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…These magnetic materials normally generate a static magnetic field (SMF), and the flux leakages spread to oral adjacent tissues (Riley et al, ; Yagci & Kesim, ). Multiple studies have investigated the biological effect of magnetic fields on alveolar bone, gingiva, and dental pulp (Bondemark, Kurol, & Larsson, ; Kim, et al, ). The Kim et al () study demonstrated that the magnetic field and osseointegration have the positive correlation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These magnetic materials normally generate a static magnetic field (SMF), and the flux leakages spread to oral adjacent tissues (Riley et al, ; Yagci & Kesim, ). Multiple studies have investigated the biological effect of magnetic fields on alveolar bone, gingiva, and dental pulp (Bondemark, Kurol, & Larsson, ; Kim, et al, ). The Kim et al () study demonstrated that the magnetic field and osseointegration have the positive correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have investigated the biological effect of magnetic fields on alveolar bone, gingiva, and dental pulp (Bondemark, Kurol, & Larsson, ; Kim, et al, ). The Kim et al () study demonstrated that the magnetic field and osseointegration have the positive correlation. Bondemark et al () indicated that there are no changes in human dental pulp or gingival tissue adjacent to the magnet implants.…”
Section: Introductionmentioning
confidence: 99%
“…COL12A1 is a protein that is a member of the fibril-associated collagens with interrupted triple helix (FACIT) collagen family, which is related to the ECM –receptor interaction, PPAR-Peroxisome proliferator-activated receptor and the MAPK-Mitogen-activated protein kinase signaling pathway ( Kim et al, 2016 ; Punetha et al, 2017 ; Zhang et al, 2018 ; Xiang et al, 2019 ). COL12A1 is associated with joint anomalies, gastric cancer, myopathies, ECM defects, and chondromyxoid fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…While it is beyond the remit of this review to discuss in details studies on implant osseointegration, it is worth mentioning that animal and human studies applying whole‐genome analyses on peri‐implant tissues and cells have also contributed to elucidate the sequence of gene activation during bone formation and they have confirmed that, while immuno‐inflammatory response‐ and ECM‐associated genes are the ones most highly expressed during the early days, the later stages of organization of the granulation tissue and formation of woven bone involve the upregulation of angiogenesis, osteogenesis and neurogenesis genes. [ 84–91 ] We previously published transcriptomic data from trephine bone core specimens retrieved together with cylindrical titanium implants from the retromolar areas of healthy volunteers at different time points (4, 7, and 14 days). Our results indicated that immune‐inflammatory pathways, such as the I‐kB kinase/nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐kB) cascade, were upregulated during the first healing days, whilst TGF‐β/BMP, Notch and Wnt signaling pathways were significantly expressed at the later healing time.…”
Section: Omics Approaches To Characterize the Bone Regeneration Procementioning
confidence: 99%